QUEST-BASED TECHNOLOGY IN CAREER GUIDANCE OF SCHOOL STUDENTS: A PRACTICAL CASE OVERVIEW - Prokopenko, Antonina; Zinchenko, Anna (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article is devoted to innovations in the organisation of modern professional orientation of schoolchildren. The authors note that different areas of social life largely contribute to the new developments in interactive educational technologies. The purpose of the article is to study the technology of a quest and review the practice of its implementation in the vocational guidance of school students. The article briefly reviews the purpose of vocational guidance regarding the needs of the modern Ukrainian labour market. The article clarifies the difference between the concepts of "quest", "educational quest", and "vocational guidance quest". The article defines the goal of a vocational guidance quest, which includes goals of the general and specialised scopes. The article employs the following research methods: theoretical (analysis of psychological, pedagogical and methodological literature on the research topic, interpretation, and generalisation of teaching experience) and empirical (observational, interactive and experimental testing of the developed quest). The study results show that an interactive game - a vocational guidance quest - is a particularly productive technology that meets the modern requirements of career guidance activities with schoolchildren. The study interprets a vocational guidance quest as a form of career guidance work that contributes to the formation of complex psychological formations of the personality together with the emotional and volitional sphere and its content, i.e. the implementation of problem-solving tasks using game technology, serves as the basis for the formation of the necessary knowledge about the professional market in general and a specific professional field in particular. The vocational guidance quest, used as an example, was developed and implemented at Sumy State University (SumDU) and described in this article, namely its structure, participants, stages of implementation, positive aspects and significance. The conclusion summarises the study’s results and postulates that the vocational guidance quest implements the trinity of learning functions: educational, cognitive and developing, besides being a career guidance activity.